Utilizing TF-IDF Content-based Filtering for Job Recommendation Systems - Sunaryo Winardi; Sunario Megawan; Ng Poi Wong; Ritchie Kurniawan; Ferry Andika Putra; Cynthia Cynthia (2025)
Abstract - The unemployment rate in Indonesia has recently shown an increase. Although many types of jobs are available, each job has specific requirements that job seekers must meet. This causes many job seekers to struggle in selecting job vacancies that match their interests and skills. To address this issue, we propose the development of a recommendation system that leverages job data to assist job seekers in finding vacancies that meet their criteria. This recommendation system employs content-based filtering using the TF-IDF (Term Frequency-Inverse Document Frequency) and Cosine Similarity algorithms, implemented using Scikit-learn's machine learning library. By analyzing job descriptions and job seekers' profiles, the system can provide job recommendations based on salary, education, skills, interests, and job location. This approach resulted in a Mean Average Precision (MAP) score of 0.798, indicating a reasonably high level of accuracy for the recommendation system overall. This result is expected to facilitate job seekers in finding the right job opportunities and reduce the unemployment rate in Indonesia.Keywords Job Recommendation System; Content-Based Filtering; TF-IDF (Term Frequency-Inverse Document Frequency; Abstrak - Tingkat pengangguran di Indonesia dalam beberapa waktu terakhir menunjukkan peningkatan. Meskipun tersedia banyak jenis pekerjaan, setiap pekerjaan memiliki persyaratan khusus yang harus dipenuhi oleh pencari kerja. Hal ini menyebabkan banyak pencari kerja kesulitan dalam memilih lowongan yang sesuai dengan minat dan keterampilan mereka. Untuk mengatasi permasalahan tersebut, penelitian ini mengusulkan pengembangan sistem rekomendasi yang memanfaatkan data lowongan kerja untuk membantu pencari kerja menemukan lowongan yang sesuai dengan kriteria mereka. Sistem rekomendasi ini menggunakan content-based filtering dengan algoritma Term Frequency-Inverse Document Frequency (TF-IDF) dan Cosine Similarity, yang diimplementasikan menggunakan pustaka machine learning Scikit-learn. Dengan menganalisis deskripsi pekerjaan dan profil pencari kerja, sistem dapat memberikan rekomendasi berdasarkan gaji, pendidikan, keterampilan, minat, dan lokasi kerja. Pendekatan ini menghasilkan nilai Mean Average Precision (MAP) sebesar 0,798, yang menunjukkan tingkat akurasi yang cukup tinggi secara keseluruhan. Hasil ini diharapkan dapat mempermudah pencari kerja dalam menemukan peluang kerja yang tepat serta membantu mengurangi tingkat pengangguran di Indonesia..Kata kunci : Sistem Rekomendasi Pekerjaan; Content-Based Filtering; TF-IDF (Term Frequency–Inverse Document Frequency;